Diretrizes, projetos, sala de aula: passos e descompassos da educação jurídica nos cursos de direito do estado de São Paulo - Mascaro, Arnaldo Braga (Universidade Federal de São Carlos, 2014)
This dissertation aims to demonstrate the steps and missteps in legal education in law courses in the state of São Paulo based on the analysis of Curriculum Guidelines and Political Pedagogical Projects (PPPs) and of their effectiveness in courses, through sampling. At this study s core is the concept that, at the level of discourse, the guidelines and PPPs are well developed and have content and methodology in accordance with the most recent findings in educational science. However, results have demonstrated the divergence between theory and practice. Taking into account that the state of São Paulo offers 220 of the nearly 1300 law degree programs available in Brazil, an analysis is performed of their necessity when less than half of college-aged Brazilians are enrolled in degree programs, a figure promised by the National Education Plan and the debate over inclusion with quality vs. exclusion. This analysis is done through a reading of the PPPs available at the Legal Education Commission of the Brazilian Lawyer s Order in São Paulo, which enabled an evaluation of the courses from 2010 to 2012, as well as interviews with members of the Commission. The present dissertation also draws from a thorough review of all law degree programs in the state of São Paulo, and their data was processed so as to be able to be accessed, altered and completed, thereby assisting researchers and the research group Education and Law in Contemporary Brazilian Society UFSCar, of which I am a member.
Keywords: Direito - estudo e ensino; Ensino jurídico; Curso de direito; Projeto político pedagógico; Legal education; Law degree programs; Political pedagogical projects; CIENCIAS HUMANAS::EDUCACAO